The Effect of Probiotic Administration with Different Time Intervals on Water Quality in Shrimp Cultivation Vaname (Litopenaeus vannamei) Biofloc System - Maulana, Rona; Diniarti, Nanda; Affandi, Rangga Idris (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Vaname shrimp is one of the marine fishery commodities that has high economic value. Water in vaname shrimp cultivation must be maintained in quality. Ammonia can be harmful to shrimp, control of ammonia and organic matter content can be done biologically with the application of probiotics. Therefore, this study needs to be conducted to determine the right time interval in providing probiotics to the water quality of vaname shrimp cultivation in the biofloc system. The method used in this study is the experimental method, using RAL with 4 treatment levels and 3 repetitions, with treatment P0 (Once during maintenance), P1 (once every 5 days), P2 (once every 10 days) and P3 (once every 15 days), the probiotic used in this study is the probiotic Probio-7. The results of the study during 56 days of maintenance showed that the average value of water quality salinity 26.7-27 ppt, temperature 27.7-28°C DO 7.13-7.16 mg/L, nitrate 0.63-0.87 mg/L and Total Ammonia 0.76-0.92 mg/L. Based on the research activities that have been carried out, the interval of probiotic administration has a significant effect on water quality. Probiotic administration can increase the Total Ammonia content and reduce the amount of ammonia in this study. Probiotic administration with an interval of 5 days once (P1) gave a total ammonia value of 0.78 mg/L with an ammonia amount of 0.067 mg/L. P1 also gave the highest growth, absolute weight 5.61 g, absolute length 8.82 cm, SGR 5.779%/Day and FCR 1.47.